Maritime Risk in Seaport Operation: A Cross-Country Empirical Analysis with Theoretical Foundations - Hyuk Soo Cho; Jung Sun Lee; Hee Cheol Moon (Asian Journal of Shipping and Logistics, 2018)
The maritime industry has witnessed several accidents worldwide. These disasters have raised the awareness of both researchers and policy makers about the importance of risk assessment and safety in marine transportation and seaport operation. This study aims at clarifying the determinants of maritime risk involved in seaport operation, based on theoretical foundations and empirical findings. From the RBV and SEM estimations, we could identify infrastructure and operational efficiency as important tangible and intangible resources, respectively, to decrease maritime risk and increase traffic volume. TCE was applied to explain theoretically the importance of operational efficiency to consignors, forwarders, and shipping companies in terms of using seaports. From the Institutional Theory, various risks involved in seaport operation could be enhanced where external institutions are uncertain or unstable. Keywords: Maritime Risk, Seaport, RBV, TCE, Institutional Theory